2020
DOI: 10.3389/fpsyg.2020.02029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Influences of College Students’ Psychological Capital in Entrepreneurial Learning Engagement

Abstract: College students' entrepreneurial learning engagement (ELE) is a key link that affects the success of future entrepreneurship. To analyze the influencing factors of the psychological capital (PC) dimension in college students' ELE, a total of 211 college students were selected from colleges in the Ningbo area for questionnaire survey. The principal component analysis method was used to test the difference validity of PC and ELE. One-way analysis of variance was used to analyze differences in demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, this section measures EP based on the enterprise’s financial indexes, such as the enterprise’s ROA, SGR, and ROI ( Rogoza et al, 2018 ; Chen, 2019 ; Wu and Song, 2019 ). It also examines some subjective indexes, including enterprise ETR and entrepreneurial self-efficacy (ESE) ( Yin et al, 2020 ; Zhang B. et al, 2020 ). EP can be divided into survival performance and growth performance in the growth process of start-ups ( Chen and Yu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this section measures EP based on the enterprise’s financial indexes, such as the enterprise’s ROA, SGR, and ROI ( Rogoza et al, 2018 ; Chen, 2019 ; Wu and Song, 2019 ). It also examines some subjective indexes, including enterprise ETR and entrepreneurial self-efficacy (ESE) ( Yin et al, 2020 ; Zhang B. et al, 2020 ). EP can be divided into survival performance and growth performance in the growth process of start-ups ( Chen and Yu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some research in recent years has discovered that some features of the familial environment, such as the bond between parents and children and the support of the family, are antecedents of PsyCap and have a big effect on it. 47 , 75 , 77 Similarly, Zhang et al 51 also point out high family income predicts higher PsyCap in individuals, as it provides material wealth that builds confidence and optimism and reflects a higher parental education level which encourages positive qualities in their children. Additionally, The outcomes from one quantitative study confirmed that there is a strong link between psychological capital and the support of parental liberty.…”
Section: Resultsmentioning
confidence: 98%
“…In general, given the same learning task, the wavelet has a simpler structure, faster convergence speed, and higher accuracy. Therefore, the wavelet NN is more suitable for the exploration of entrepreneurial psychology affected by human factors, and the prediction results can be dynamically updated in real-time (Zhang et al, 2020 ).…”
Section: College Students' Entrepreneurial Psychologymentioning
confidence: 99%